Biphenotypic leukaemia: a case of mixed T lymphoblastic and myeloblastic leukaemia. Issue 5 (May 1985) - Morgan, M A; Scott, C S; Tavares de Castro, J; Limbert, H J; Polli, N; Catovsky, D; Pyrah, R D; Roberts, B E
Abstract : A case of mixed acute leukaemia with T lymphoblastic, myeloblastic, and monocytic components is described. The use of immunological markers, ultrastructural morphology, cytochemistry, immunochemistry, and combined techniques, simultaneously detecting two markers in individual cells, made it possible to define the different blast cell populations.